FAIRCLOUGH, N. New labor, new language? London: Routledge, 2000, 178 p. - Ferreira, Erika (Cadernos de Linguagem e Sociedade, 2010)
FAIRCLOUGH, N. New labor, new language? London: Routledge, 2000, 178 p.